A review on causes of cost overrun in the construction projects - Albtoush, Faten Ahmad; Doh, Shu Ing (IJNIET, 2019)
Cost overrun is a frequent phenomenon in the construction projects in all countries, whether it developed or developing country. This problem is critical issues that affect project success. Thus it requires serious attention from all participants in construction projects to keep the projects in safe mode, to be completed within its limited cost, time and quality. Cost overrun have negative impact in performance of construction projects, that because construction industry is huge and complex. Any problem occurs through the life cycle of project lead to other problem in different parts of project. Through literature review many researchers studies cost overrun and indicated the most causes of cost overruns according to their studies. The current study aims to highlight the most causes of cost overrun in construction projects. These causes are classified into ten main groups according to their sources, namely: Design and contract related factors, Estimation related factors, Planning and Schedule related factors, Project Management related factors, Labor related factors, Financial related factors, Material and Machinery related factors, Construction Phase related factors, Communication Related Factors, External related factors. The importance of current research is to summarize the most important causes of cost overruns in construction projects, thus helping project participants to identify the sources of these factors to address them and mitigate their negative effects.